Desenvolvimento de software para monitoramento de escoamento bifásico utilizando transdutor a fibra óptica - Mazzo, Paulo Henrique Ruiz (2022)
This work presents the development of a software in Python programming language to act in conjunction with an optical and electrical probe to monitor two-phase flow. Through the software, it is possible to identify the sensitivity of the probe. In addition, the software can auto-calibrate the probes, simulate new probes from the mathematical models developed, perform the data acquisition and display a real-time graph. Combining the developed program with the interrogator, we have a system that is easy to use and offers the possibility of unscheduled intervention, if necessary, making it more advantageous for the operator to monitor the flow.